2010
DOI: 10.1111/j.1364-3703.2010.00659.x
|View full text |Cite
|
Sign up to set email alerts
|

Infection of Arabidopsis thaliana by Phytophthora parasitica and identification of variation in host specificity

Abstract: Oomycete pathogens cause severe damage to a wide range of agriculturally important crops and natural ecosystems. They represent a unique group of plant pathogens that are evolutionarily distant from true fungi. In this study, we established a new plant-oomycete pathosystem in which the broad host range pathogen Phytophthora parasitica was demonstrated to be capable of interacting compatibly with the model plant Arabidopsis thaliana. Water-soaked lesions developed on leaves within 3 days and numerous sporangia … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
89
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(93 citation statements)
references
References 57 publications
4
89
0
Order By: Relevance
“…Most of these lines, including Ws-4, did not show necrosis after CBEL treatment. While Arabidopsis natural variability of resistance to bacterial and fungal pathogens has been documented for some pathogens including Phytophthora (Denby et al , 2004; Birker et al , 2009; Attard et al , 2010; Nemri et al , 2010; Wang et al , 2011), natural variability to necrotic elicitors has not been explored. The current results suggest that necrotic response to CBEL cannot be generalized to the A. thaliana species.…”
Section: Discussionmentioning
confidence: 99%
“…Most of these lines, including Ws-4, did not show necrosis after CBEL treatment. While Arabidopsis natural variability of resistance to bacterial and fungal pathogens has been documented for some pathogens including Phytophthora (Denby et al , 2004; Birker et al , 2009; Attard et al , 2010; Nemri et al , 2010; Wang et al , 2011), natural variability to necrotic elicitors has not been explored. The current results suggest that necrotic response to CBEL cannot be generalized to the A. thaliana species.…”
Section: Discussionmentioning
confidence: 99%
“…Bacteria usually penetrate via natural opening such as stomata, and stomatal closure can essentially restrict bacterial invasion (Melotto et al 2006). Phytophthora pathogens can also penetrate via stomata but, instead, they prefer to penetrate at the junctions between epidermal cells (Hardham 2007;Wang et al 2011). Therefore, the function of LecRK-V.5 in suppressing stomatal immunity is dispensable for preventing Phytophthora penetration.…”
Section: Discussionmentioning
confidence: 97%
“…To determine the involvement of other LecRK in Phytophthora resistance, we performed infection assays on the LecRK T-DNA insertion lines with P. brassicae, P. capsici, and P. parasitica. Recently it was reported that the latter two are able to infect Arabidopsis (Wang et al 2011(Wang et al , 2013.…”
Section: Response Of Lecrk T-dna Insertion Lines To Phytophthora Pathmentioning
confidence: 99%
“…For instance, penetration of host tissues by Phytophtora sp . has been only recently characterized morphologically, and very little is known about the underlying molecular mechanisms [5,6]. …”
Section: Model Invasive Structuresmentioning
confidence: 99%
“…Furthermore, these myosins contribute to developmentally regulated organization of the F-actin bundles in the growing root hairs; in some multiple knockouts of myosin genes, the depolarization/branching defects (analogous to those seen when AtFH8 is up-regulated) were described [4]. Given that several plant myosins are expressed specifically in pollen [6], it seems likely that the myosins are indispensible for pollen tube growth as well. Although polar growth of the budding yeast cells cannot be considered invasive, it also relies on myosin V closely related to plant myosins XI [7].…”
Section: Reviewers Commentsmentioning
confidence: 99%